Analysis of The Calculation of The Cost of Production Based on The Full Costing Method as The Basis For Determining The Selling Price on The CV. Cita Mandiri Batu City - Prasetio Natara; Elly Lestari; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study is to analyze the calculation of the cost of production based on the full costing method as the basis for determining the selling price on CV. Cita Mandiri Batu City. This research uses a qualitative method. The data used was an interview with the leader and one of the employees in the production field at CV. Cita Mandiri Batu City. The data analysis method used is descriptive with the cost of production based on the full costing method. The results of the analysis prove that the cost of production is based on the full costing method in one production on CV. Cita Mandiri Kota Batu as much as IDR 3,384,500 with the determination of the selling price of potato chips per package of 100 grams at a price of IDR 18,000. These results prove that CV. Cita Mandiri Kota Batu has been optimal in determining the selling price because it made a profit of IDR 935,500 or as much as 27,64% in one production. The calculation of the cost of production using the full costing method is able to increase the accuracy in determining the selling price of products.